Hadis dalam Budaya Indonesia Abad XVII-XVIII - Wahyuni Shifatur Rahmah (LPPM IAINU Kebumen, 2020)
Studies on the development of Hadith Thought in Indonesia are rare. However, it does not mean that it did not develop at all, because the study of hadith at the beginning of the entry of Islam in Indonesia at that time was only an anthology that is a collection of various themes related to the study of jurisprudence, so it is still mixed with other disciplines. This study reveals the development of hadith thought in the XVII and XVIII centuries, especially the thought of 'Abd Rauf Al-Sinkili, who represented the scholars at that time. Through the description of the analysis of this research shows that hadith at that time has not developed into a separate discipline, Because the study of new hadith on the plains, not theoretically arranged. Proven by the publication of Al-Sinkili's work on hadith; the first Syarah Latif 'ala Arba'in Hadith li Imam an-Nawawi, which is an interpretation of 40 hadiths by al-Nawawi, the second is al-Mawa'iz al-Badi'ah, a collection of hadith qudsi, which is the revelation of God delivered to the believers through the words of the Prophet Muhammad SAW. In his study of Hadith, Al-Sinkili sought to reflect the efforts to make the ways of the Prophet - in addition to the teachings of the Qur'an - not only a source of law, but also an inexhaustible inspiration for worthy moral practices.